Topology-dependent pH-responsive actuation and shape memory programming for biomimetic 4D printing - Pan, Matthew Houwen (2023)
Biomimetic actuators are critical components of bionics research and have found applications in the fields of biomedical devices, soft robotics, and smart biosensors. This paper reports the first study of nanoassembly topology-dependent actuation and shape memory programming in biomimetic 4D printing. Multi-responsive flower-like block copolymer nanoassemblies (vesicles) are utilized as photocurable printing materials for digital light processing (DLP) 4D printing. The flower-like nanoassemblies enhance thermal stability, attributed to their surface loop structures on the shell surfaces. Actuators prepared from these nanoassemblies display topology-dependent bending in response to pH and temperature-programmable shape memory properties. Biomimetic octopus-like soft actuators are programmed with multiple actuation patterns, large bending angles (≈500°), excellent weight-to-lift ratios (≈60), and moderate response time (≈5 min). Thus, nanoassembly topology-dependent and shape-programmable intelligent materials are successfully developed for biomimetic 4D printing.